Economic Value Added and Corporate Financial Performance: Empirical Evidence from PT. Argamas Jaya Lab - Hanum Yulia; Rahmadi Rahmadi; Tora Fahrudin (Al Dzahab, 2026)
Purpose: This study aims to evaluate the financial performance and value creation of PT. Argamas Jaya Lab has been using the Economic Value Added (EVA) approach for over five years. Design/Methodology/Approach: This research employs a quantitative descriptive approach by analyzing the company’s financial statements from 2019 to 2023. Financial performance is assessed through the calculation of Economic Value Added (EVA), which incorporates key components such as Net Operating Profit After Tax (NOPAT), Invested Capital, and Weighted Average Cost of Capital (WACC). Data were obtained from company financial reports and supporting documentation to ensure the reliability of secondary data. Findings: The results indicate that the company’s EVA fluctuated during the observation period, reflecting variations in NOPAT, invested capital, and the cost of capital. The findings suggest that the EVA approach provides a more comprehensive assessment of corporate financial performance and value creation compared to traditional accounting-based performance indicators, as it explicitly considers the cost of capital in measuring economic profit. Research Implications: This study contributes to the financial management literature by highlighting the relevance of EVA as a value-based performance measurement tool, particularly in sectors where its application remains limited. The findings also provide practical insights for managers and investors in evaluating corporate financial performance and supporting strategic decision-making aimed at improving value creation.